PROFIL KEBUGARAN FISIK PELAJAR SLTA DI KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Suharjana Suharjana (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractThis study aims to describe the profile of the physical fitness of Senior HighSchool students in Kulonprogo Regency, Yogyakarta Special Territory. The resultsof the study are expected to serve as inputs for physical education teachers in thelearning assessment. The results can also be used by educational policy makers inthe curriculum development to take into account of students needs. For students,the results can be used in the reflection to improve their physical fitness and thingsto consider in their active life. This study was a survey study employing a test. Theresearch population consisted of male and female students of Senior High Schoolsin Kulonprogo Regency, Yogyakarta Special Territory. The sample comprised 410students from private and public Senior High Schools, consisting of 235 malestudents and 175 female students. The sample was selected using the multistagerandom sampling technique. The research variable was the profile of the physicalfitness, which was collected using the Copper test by asking the students to runaround the field for the 2.4 km. The data were analyzed by the descriptivetechnique employing the percentage. The study concludes that the studentsphysical fitness is in the category of lack of physical fitness, occupied by 232students (56.6%). The following suggestions are proposed. First, further studiesshould involve other variables, not only the physical fitness, such as the profile ofthe health, including the variables on the body fat, level of glucose, tension andheartbeat. Second, further studies should use other instruments, such as theMultistage Fitness Test or the test of stepping up and down the bench as acomparison.Keywords: physical fitness, Cooper Test